A New Strategy for Presbycusis: A Literature Review on Stem Cell Thera-Py for Hair Cell and Auditory Neuron Regeneration - Puspanadi, Theresa; Sugianto, Paulus; Limantara, Edward; Metaputra , Teguh Filbert (Indonesian Health Journal, 2025)
Presbycusis, or age-related hearing loss, is the leading cause of hearing loss among the elderly, leading to decreased quality of life and mental health issues. While existing treatments offer some benefits, they have limitations and do not address the degenerative nature of presbycusis. This literature review examines the regenerative potential of stem cell therapy and its derivatives for cochlear hair cells and auditory neurons in cases of presbycusis. A search was conducted across PubMed, ScienceDirect, and Google Scholar to identify literature published from 2020 to 2025 that studied stem cells and their derivatives for hair cell and auditory neuron regeneration in presbycusis models. Three preclinical studies using bone marrow-derived mesenchymal stem cells (MSCs) in rodent models demonstrated the regeneration of hair cells and auditory neurons, with evidence of hearing improvement. Each study employed unique MSC modifications using advanced techniques, such as gene editing and extracellular vesicle derivation, to enhance anti-inflammatory and antiapoptotic properties. Stem cell-based therapies for presbycusis show promise but remain in early developmental stages. Major challenges include optimizing delivery methods (intracochlear, intratympanic, or intravenous routes), ensuring long-term safety profiles, preventing immune rejection and tumorigenicity, establishing standardized protocols for cell preparation and dosing, and addressing high treatment costs. Further clinical and local research is essential to facilitate the implementation of this therapy in Indonesia.